Morphology of the last subaerial unconformity on a shelf: insights into transgressive ravinement and incised valley occurrence in the Gulf of Cádiz - Lobo, Francisco J.; García, M.; Luján, M.; Mendes, Isabel; Reguera García, M. Isabel; Rooij, David van (Geo-Marine Letters, 2020)
The main aim of this study is to explore the spatial patterns of the shelf-scale erosional unconformity related to the last glacial maximum (LGM), particularly in terms of the role of underlying geology and the presumed primary influence of sea-level changes. This involved a detailed mapping of the most recent and widespread erosional shelf surface in a sector of the northern margin of the Gulf of Cádiz (northeast Atlantic Ocean) located adjacent to a major fluvial source. A dense network of high-resolution seismic profiles collected in the 1990s and 2013 off the Guadiana River revealed two distinct geomorphological domains on the LGM shelf-scale subaerial surface. The outer domain exhibits a widespread occurrence of erosional truncations, with a rugged, erosional pattern over the most distal shelf setting that evolves landward into a planar unconformity. The inner domain is more extensive and is characterized by the common occurrence of highly reflective, localized mounded seismic facies that laterally evolve into an irregular surface and in places may develop a channelized morphology. Significant fluvial incision is limited to a major straight valley and a secondary distributary channel. A distinct partition of the lowstand surface is documented, and attributed to a well-marked lithological change. A coarse-grained inner shelf comprises underlying lithified coastal deposits, whereas a fine-grained outer shelf is regarded as the uppermost expression of regressive prodeltaic wedges. The influence of regional indurated surfaces is also expressed in (1) the pattern of erosion, this being more patchy on the inner shelf due to lateral changes of erodibility, whereas on the outer shelf it shows laterally continuous bands, owing to different modes of transgressive ravinement; (2) the spatial and temporal variability of fluvial incision. Inner shelf armoring by indurated deposits prevents reoccupation of previously incised valleys. Instituto Andaluz de Ciencias de la Tierra, Consejo Superior de Investigaciones ...